FUSTIGATION IMPOLITENESS, EMOTIONS AND EXTIMACY IN ARGENTINE MEDIA CELEBRITIES - Silvia Kaul de Marlangeon (Russian journal of linguistics: Vestnik RUDN, 2018)
The aim of this paper is to examine the connection among fustigation impoliteness - a type of impo-liteness within Kaul de Marlangeon’s (2005, 2008) and Kaul de Marlangeon & Alba-Juez (2012) taxono-my of impolite acts, emotions and extimacy, focusing on Argentine media celebrities of the Río de la Plata cultural context. This article highlights the phenomenon of speaker’s or hearer’s extimacy as a vo-litional form within an aggressive relationship, used for the promotion of the speaker’s ego through me-dia exhibitionism that enlarges one’s own and others’ intimacy and sharing with the public. Within a prag-matic sociocultural approach, this work intends, on the one hand, to investigate fustigation impoliteness as a usual practice of violent public interactions of media celebrities, and on the other hand to consider when such expressions are due to the extimacy of the speaker or to that attributed to or imposed on the hearer or on a third party by the speaker.